Modification of epoxy with Polyaniline and its effects on cathodic disbondment factors - Rahman, N.A.A. (Asian Research Publishing Network, 2016)
The tendency of the external coating of underground pipeline to disbonded is highly due to the service environment. The inadequate coating also becomes one of the contributing factors in the disbonded of an underground pipeline. The function and desired characteristics of an external coating are very important issues. In this work, the performance of Polyaniline (PANI) in epoxy coatings has been investigated by performing the cathodic disbonding test. Varies concentration of PANI was used to find the lowest disbonded radius. The test was carried out at two differents conditions for the comparisons purpose. The results were compared with previously stated effects of the potential, time, pH of NS4 soil solution. It was found that the cathodic disbonding radius decreased with increase the PANI content in the epoxy coating system. Â© 2006-2016 Asian Research Publishing Network (ARPN).